Exploration of the theoretical perspectives of community organization, social talent and leadership: starting points from which to promote social change - Cervantes Arreola, Diana Irasema; Elías Hernández, Juan Andrés; Anguiano Escobar, Beatriz (Universidad Francisco de Paula Santander, 2025)
An exploration of the theoretical perspectives of communal organization, social talent and leadership is presented and how from these perspectives, social change can be promoted. This document integrate the visions from which to reflect on this topic, with the view that it is assumed as the best starting point for issues of social change. The latter is prevailing in our times, so exploration from different positions helps to visualize the best way to promote it. The communal organization represents a construct of community thinking, to build a collective horizon; On the other hand, social talent allows the cohesion of people, where through various personal and sociocultural elements, it can be linked with the experiences of others for the transformation of social spaces. Finally, leadership has to do with those capabilities that enable move people, in search of a common goal, with certain actions that the person leading propose for follow-up. With this, a panorama opens from the vision of the three theoretical perspectives, generate a reflection on the aspects related to social change and its frameworks, allowing them to be taken as starting points for those who are interested in social changes and those who wonder about the different perspectives.